Technical writing, presentation skills, and online communication : professional tools and insights - Greenlaw, Raymond (Information Science Reference, 2012)
"This book is a collection of work to assist any professional who needs to deal with ethical issues, write up a technical project, give or develop a presentation, or write material for an online audience"--Provided by publisher.